Sustainable waste and cost reduction strategies in a strategic buyer-supplier relationship. (10th November 2019) - Yoo, Seung Ho; Rhim, Hosun; Park, Myung-Sub
Abstract: We investigate incentive schemes for a sustainable waste and cost reduction activity in a dyadic supply chain. The buyer motivates the internal operations department and external supplier to reduce the supply chain's overall production cost by reducing the waste and energy consumption. By incorporating players' risk aversion and opportunity loss as in practice, we construct three benefit-sharing models: two cost target models to maintain unit profit and profit ratio (UP and PR) and one with no target (NT). Then, we reveal that the benefit-sharing scheme yielding superior cost performance varies depending on the market situation and the relationship intensity between players. In a highly strategic buyer-supplier relationship, the NT scheme yields the best result if the supply chain maintains a low profit ratio. The PR scheme is superior with the high original profit ratio. When the buyer maintains a transactional relationship with the supplier, adopting the UP scheme always guarantees superior cost reduction performance. Highlights: We consider collaborative waste and cost reduction based on target costing. Three benefit sharing strategies are modeled based on the principal-agent paradigm. Models include two target cases and one without target. The performance varies depending on the market and the relationship intensity. We reveal the conditions under which each strategy outperforms others.